TAX AND DEVELOPMENT: EXAMINING THE ROLE OF TAXES IN ACCELERATING ECONOMIC GROWTH - Loso Judijanto; Wigianto Budiawan; Bambang Triyono; Al-Amin (INTERNATIONAL JOURNAL OF SOCIAL AND EDUCATION, 2024)
Taxes are mandatory contributions from citizens to the government that are used to finance development. Through effective tax collection, the government can allocate funds for infrastructure, education, health, and other public services. Appropriate, transparent, and fair tax policies can increase economic growth and support sustainable development, political stability, and international cooperation. The research method used in this study is literature. The results show that political stability and consistent government commitment to tax reform are essential. Public trust in tax funds and a much more educated culture are also important factors that increase public participation and compliance. In addition, international cooperation in information and law enforcement is also important to address global challenges, including tax evasion and transfer pricing.